ANALISIS KESEHATAN KOPERASI SIMPAN PINJAM SWAMITRA CITRA NIAGA SAMARINDA - Nora Edang, Gabriella Novita (EKONOMIA, 2017)
The development of cooperative activities in Indonesia hence the demand for cooperative management to be carried out in a more professional manner will be greater. In particular pay attention to the financial and management aspects that need to be managed professionally in accordance with prudential principles and health of savings and loan cooperatives, so as to increase trust and provide maximum benefits to the members and surrounding communities. One of them on the Savings and Loans Cooperative Swamitra Citra Niaga Samarinda seen in 2014 to 2016 has decreased about 47% -50%. The purpose of this research is to know the health of Swamitra Citra Niaga Samarinda Savings and Loans Cooperation in 2014 until 2016 based on the Regulation of Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No. 06 / Per / Dep.6 / IV / 2016. Analyzer used is capital aspect, productive asset quality aspect, management aspect, efficiency aspect, liquidity aspect, independence aspect and growth aspect, and aspect of cooperative identity. The results concluded from the seven aspects considered that the health of Swamitra Citra Niaga Savings Cooperative in 2014 until 2016 in the predicate